Factors Affecting Progonosis in Tuberculous Meningoencephalitis - Puspitasari, Vivien; Sutanto, Anyeliria; Stevano, Reza; Djuanda, Gerald (Acta Neurologica Indonesia, 2023)
Introduction: Cases of tuberculosis is still highly prevalent in the world, including Indonesia.Tuberculous meningoencephalitis (TBME) is the most severe form of tuberculosis. This study aims to establish the factors affecting prognosis in TBME. Objective: To Identify the clinical factors that affect the prognosis of tuberculous meningoencephalitis patients. Material and Methods: This is cross-sectional study evaluating factors (clinical features, imaging, and treatment) affecting prognosis in TBME patients who underwent treatment in Siloam Hospitals Lippo Village. Univariate analyses was done, followed by bivariate analyses with logistic regression to compare factors between good (Glasgow outcome scale [GOS] 4-5) and poor (GOS 1-3) prognosis. Results and Discussion: 64 patients were included. On univariate analysis, significant differences was found between Glasgow coma scale (GCS) scores (p=0.012), clinical features of meningeal irritation (p=0.004), findings of hydrocephalus (p=0.023) and vasculitis/infarction (p=0.020) on imaging, antibiotic use (p=0.013), and MRC grading (p=0.008). On logistic regression, 4 factors were found to be significant: headache (OR 5.398 95% CI 1.165-25.008, p=0.031), meningeal irritation (OR 0.146 95% CI 0.026-0.813, p=0.028), hydrocephalus (OR 0.167 95% CI 0.032-0.881, p=0.035), and antibiotic use (OR 0.155 95% CI 0.034-0.717, p=0.017). Conclusion: Clinical manifestations of meningeal irritation and altered consciousness, imaging findings of hydrocephalus and vasculitis/infarction, and antibiotic usage is associated with poor prognosis, while presence of headache is associated with a better prognosis.